Smoking cessation: aspects of prevention and therapy. The activity ofthe Smoking Cessation Center of Parma - Italy - Mariano, M. E.; Elia, D.; Scarascia, A.; Tzani, et al., P. (Acta Biomedica Atenei Parmensis, 2009)
The World Health Organization states that only a reduction in tobacco use would lower the number of deaths from cancer. It is possible to decrease the number of deaths by means of prevention and/or smoking cessation. Smoking cessation therapy includes both psychological support and pharmacological treatment: Nicotine Replacement Therapy (NRT), Bupropion Sustained-Release, and Varenicline. The aim of the Smoking Cessation Center of Parma is to provide instruments, methodologies and individual therapies for achieving abstinence or a decrease in tobacco use. The program of the Smoking Cessation Center consists in eight meetings. During the first meeting the smoker undergoes a medical check up, and smoking history, exhaled single breath CO and dependence of nicotine are recorded and a personal therapy is planned. During each follow-up visit (after 15 days and then at 1,2,3,6,9 and 12-month intervals) the compliance of the patient to the treatment and abstinence symptoms are assessed. Since 2000, we achieved tobacco abstinence in 28% of patients. Combined treatment (Bupropion/ NRT) provided a higher percentage of success (39,9%).